Results of the measurement of SOFC fuel cell stacks under pressure conditions. Issue 1 (May 2021) - Berg, H.P.; Dückershoff, R.; Vorpahl, M.; Himmelberg, A.
Abstract: Results from the measurement of SOFC fuel cell stacks under pressure conditions are presented. As part of a measurement campaign, the operation of a stack system is investigated, particularly under the operating conditions of a recuperated micro gas turbine. Above all, the performance and effectiveness of selected stack types at various operating pressures and operating temperatures are measured. With the test facility set up for such investigations, cell systems could be examined under atmospheric conditions and with pressures of up to 5 bar. It is shown that in operating conditions under pressure, the output of the fuel cell systems are improving. From a gauge pressure of 4 bar, the performance curve is flattened and higher pressures only produced a marginal increase in performance. Furthermore, the cells tested at overpressure show a steady-state behavior more quickly under load change requirements than in atmospheric operation. This means that more flexible operating modes with faster response behavior can be realized. By choosing a suitable operating temperature, the efficiency of the system is further increasing. Care was taken to select the operating conditions of the cell systems so that coking can be prevented. Finally, a statement can be made about the pressure dependence of the fuel conversion rate. Parasitic reactions at the anode can be related to the power output. The tests carried out have shown that the high-temperature fuel cell is a promising service provider of the future. A combination of SOFC high-temperature fuel cells and micro gas turbines in one machine could, in addition to the internal provision of the required pressure, also lead to better dynamics of the entire system and increase the energy yield from the primary energy source.